Cross Stitch Dinosaurs and Monsters - Greenoff, Jane (Newton Abbot, Devon David&Charles, 1994)
Cross-stitch project patterns for children under 10.
Include Color Illustration and Index
Keywords: Cross-stitch -- Dinosaurs in art